Optimization of Accounting information System in Public Sector for Sustainable Risk Management Under Big Data Analytics. Does forensic Accountants’ Skill Generate Differences? - HUY Pham Quang; PHUC Vu Kien (Foundations of Management)
This article sets its sight to allot an intelligible picture of how to optimize accounting information system (AIS) in public sector organization (PSO) for sustainable risk management (SRM) under the big data analytics (BDA) and offers in-depth understandings concerning to the role of forensic accountants’ skill (FAS) on these aforementioned interconnections. The structural equation modeling (SEM) and multi-group SEM were wielded to testify the hypothesized model rested on cross-sectional data formulated by a closed-ended questionnaire survey distributed to convenience and snowball sample of 683 respondents in PSOs. All the proffered hypotheses in the theoretical model were authenticated by the soundly statistical evidences. The observations of the current study also generated the numerous practical implications for the practitioners in organizational management and policymakers in building up the strategies and promulgating rules in relation to digital initiatives adoption, accounting practices and risk management toward sustainable development within PSOs.